Assessing access problems in online media platforms - Inge Graef; Sih Yuliana Wahyuningtyas; Peggy Valcke (International Telecommunications Society (ITS), 2014)
Online media platforms have the characteristics of a particular type of market known as 'multi-sided'. These businesses create value by bringing advertisers and users together. Access to user data is critical to this process. On the basis of economic literature, the features of multi-sided platforms will be discussed. It will be argued that the characteristics of multi-sided platforms increase the likelihood that successful companies become dominant due to the existence of indirect network effects. In these circumstances, dominant platforms may foreclose competition by raising barriers to entry in the large collections of user data. This may give rise to access problems for competitors and new entrants that need access to data gathered by dominant platforms in order to provide competing or complementary services. A comparative legal analysis will be used to assess the standards that apply in the United States (US) and the European Union (EU) for finding liability for refusals to deal under antitrust or competition law. The private antitrust cases that have already occurred regarding access to user data in the US show that the scope of applicability of the essential facilities doctrine is very limited after the judgment of the Supreme Court in Trinko. Although the European Commission and the Court of Justice seem to be willing to accept liability for a refusal to deal more easily than their US counterparts, high legal hurdles still have to be met under the essential facilities doctrine in the EU. Nevertheless, there are scenarios in which liability for refusals to give access to data will likely be accepted in the EU.
Keywords: 330; Multi-sided platforms; access regulation; user data; essential facilities; search engines; online social networks; e-commerce platforms